Analisis Pencapaian Cut-Off Time pada Trail Running: Perbandingan Kategori 5k dan 10k Event Merapi-Merbabu De Trail - fikri rhumba fikri rhumba; Siti Baitul Mukarromah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the profile of participants’ success in achieving the Cut-Off Time (COT) in trail running, to compare patterns of COT achievement, and to provide technical recommendations for organizers in establishing more data-driven COT standards in order to enhance safety, competitive fairness, and operational efficiency of the event. The research method employed is a quantitative descriptive approach, which seeks to objectively illustrate the achievement of COT in trail running events. The subjects of this study were all participants in the 5K and 10K categories of the Merapi-Merbabu de Trail event. The results indicate that the success profile of runners in meeting the COT is influenced by demographic characteristics and endurance capacity, with higher success rates observed in the productive age group and a decline in older age groups. The comparison of COT patterns reveals variations in time achievement across different course segments, which are correlated with route difficulty, elevation conditions, and environmental factors. Therefore, COT should not be considered uniform but rather adjusted according to the specific characteristics of the terrain Keywords: Cut-Off Time, Participant Success Profile, Trail Running